The Anatomic Features of Müller’s Muscle: A Histology Study in Chinese - Zhang, Minchen (Plast Reconstr Surg Glob Open, 2021)
The purpose of this article is to clarify the character of Müller’s muscle in Chinese specimens. METHODS: Ten upper eyelids of 10 formalin-fixed Chinese cadavers (9 elderly people, from 68 to 86 years of age; 1 male child, 10 years old) were examined. Full-thickness sagittal sections of the central part of the upper eyelids were microscopically examined using hematoxylin-eosin, Masson trichrome, and anti–smooth muscle actin antibodies staining. RESULT: In 9 elderly specimens, Müller’s muscle inserted onto tarsus via fibers, and the smooth muscle components decreased gradually and even faded away from the originated inferior branch of levator palpebrae superioris muscle to the upper margin of tarsus, although, in 1 child specimen, Müller’s muscle inserted directly onto tarsus rather than connective fibrous structure, and smooth muscle components did not decrease obviously. Both in elderly and young specimens, the aponeurotic structure that originated from Müller’s muscle extended to the tarsal plate. CONCLUSION: This study suggests that Müller’s muscle inserts onto the tarsus via fibrous tissue or smooth muscle, and also indicates that the smooth components of Müller’s muscle may decrease gradually in elderly people.